Quality of the peat water and its association with public health problems in the community of the Danau Tundai area - Nawan, Nawan; Priskila, Hopelyanza; Shinta, Herlina Eka; Septi Handayani; Ravenalla Abdurahman (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2023)
Background: Communities in the Danau Tundai Area, Palangka Raya City, Central Kalimantan Province, Indonesia still use peat water for their daily water needs. The use of peat water is one of the things that need to be considered because disease transmission can occur through water with poor quality and will cause health problems in the Danau Tundai community. Objective: This study aimed to determine the quality of peat water in the Danau Tundai Area and to identify the association between the quality of peat water and public health problems in the Danau Tundai Area Methods: Water samples taken were analyzed physically, chemically, and biologically by government water quality regulations. The primary data source in this study was a questionnaire to obtain data on peat water use and health problems among the people of Danau Tundai Results: Results indicated that peat water quality of the Danau Tundai Area didn’t meet the Ministry of Health standard for drinking water because the physical appearance was brown, tasted, and smells. The chemical analyses also showed that the levels of KMnO4 were 257.5 mg/L, Fe 0.66 mg/L, pH 4.02, Dissolved Oxygen (DO) 5.9 mg/L, Biological Oxygen Demand (BOD) 18.6 mg/L, and Chemical Oxygen Demand (COD) 156.9 mg/L. Those levels were higher than the cut-off points set by Ministry of Health. The public health problems that mostly experienced was itching (75.3%), stomachache (66.7%), and yellow teeth (61.3%). Simple linear regression showed a positive significant association between quality of peat water (based on individual perception) and public health problems in the Danau Tundai area (p = 0.000). Conclusion: Peat water quality of the Danau Tundai Area didn’t meet the Ministry of Health standard for drinking water, and the quality of peat water had a significant association with health problems Danau Tundai communities.